Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
PHUONGLYNH

Tính hợp lí :

\(\left(3-\dfrac{2}{5}+\dfrac{2}{11}\right)-\left(4-\dfrac{7}{10}-\dfrac{5}{11}\right)-\left(5-\dfrac{4}{11}+\dfrac{3}{10}\right)\)

\(\left(5+\dfrac{1}{5}-\dfrac{2}{9}\right)-\left(2+\dfrac{5}{6}-2\dfrac{3}{35}\right)-\left(8+\dfrac{2}{7}-\dfrac{1}{18}\right)\)

\(\dfrac{4}{9}:\left(-\dfrac{1}{7}\right)+6\dfrac{5}{9}:\left(-\dfrac{1}{7}\right)\)

HT.Phong (9A5)
9 tháng 2 2024 lúc 11:46

\(\left(3-\dfrac{2}{5}+\dfrac{2}{11}\right)-\left(4-\dfrac{7}{10}-\dfrac{5}{11}\right)-\left(5-\dfrac{4}{11}+\dfrac{3}{10}\right)\)

\(=3-\dfrac{2}{5}+\dfrac{2}{11}-4+\dfrac{7}{10}+\dfrac{5}{11}-5+\dfrac{4}{11}-\dfrac{3}{10}\)

\(=\left(3-4-5\right)+\left(\dfrac{2}{11}+\dfrac{5}{11}+\dfrac{4}{11}\right)+\left(\dfrac{7}{10}-\dfrac{3}{10}-\dfrac{2}{5}\right)\)

\(=-6+\dfrac{11}{11}+\left(\dfrac{2}{5}-\dfrac{2}{5}\right)\)

\(=-6+1+0\)

\(=-5\)

__________________

\(\left(5+\dfrac{1}{5}-\dfrac{2}{9}\right)-\left(2+\dfrac{5}{6}-2\dfrac{3}{35}\right)-\left(8+\dfrac{2}{7}-\dfrac{1}{18}\right)\)

\(=5+\dfrac{1}{5}-\dfrac{2}{9}-2-\dfrac{5}{6}+\dfrac{73}{35}-8-\dfrac{2}{7}+\dfrac{1}{18}\)

\(=\left(5-2-8\right)+\left(\dfrac{1}{5}+\dfrac{73}{35}-\dfrac{2}{7}\right)+\left(-\dfrac{2}{9}-\dfrac{5}{6}+\dfrac{1}{18}\right)\)

\(=-5+2+\left(-1\right)\)

\(=-4\)

__________________

\(\dfrac{4}{9}:\left(-\dfrac{1}{7}\right)+6\dfrac{5}{9}:\left(-\dfrac{1}{7}\right)\)

\(=\dfrac{4}{9}\cdot\left(-7\right)+6\dfrac{5}{9}\cdot\left(-7\right)\)

\(=\left(-7\right)\cdot\left(\dfrac{4}{9}+6\dfrac{5}{9}\right)\)

\(=\left(-7\right)\cdot\left(\dfrac{4}{9}+6+\dfrac{5}{9}\right)\)

\(=\left(-7\right)\cdot\left(\dfrac{9}{9}+6\right)\)

\(=\left(-7\right)\cdot7\)

\(=-49\)